2023
DOI: 10.1186/s12888-023-04906-6
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-associated impact and post-traumatic stress symptoms 39 days after pandemic in a sample of home-quarantined Chinese college students: the mediating effecting of past stressful events, psychological resilience, and social support

Abstract: Background During the COVID-19 outbreak, most Chinese college students were home-quarantined to prevent the spread of the virus. COVID-19-associated impact has been shown to be a risk factor for the development of post-traumatic symptoms disorder (PTSD). However, little is known about the psychological processes that mediate this association. This study investigated the association between COVID-19-associated impact and PTSD and examined whether past stressful events, psychological resilience, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…Specifically, our findings suggest that social support mediate the relationship between attachment styles and mental health state. This is consistent with previous studies that have shown similar mediation effects in different contexts, such as the association between COVID-19 and post-traumatic stress symptoms ( Zeng et al, 2023 ), attachment avoidance and depressive symptoms in college students ( Zhu et al, 2016 ), and chronic diseases and positive mental health ( Yang and D’Arcy, 2022 ). In the current study, attachment style was chosen to be an independent variable, as it is thought to develop in early life and remain relatively stable ( Fraley, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, our findings suggest that social support mediate the relationship between attachment styles and mental health state. This is consistent with previous studies that have shown similar mediation effects in different contexts, such as the association between COVID-19 and post-traumatic stress symptoms ( Zeng et al, 2023 ), attachment avoidance and depressive symptoms in college students ( Zhu et al, 2016 ), and chronic diseases and positive mental health ( Yang and D’Arcy, 2022 ). In the current study, attachment style was chosen to be an independent variable, as it is thought to develop in early life and remain relatively stable ( Fraley, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…This may lead to turnover and a lack of senior nurses in the nursing profession ( 11 ). One piece of research on PTSD in nurses during a pandemic suggests that nurses are at a higher risk of developing PTSD and should be given the necessary attention ( 12 ). Therefore, after the full liberalization of the epidemic prevention and control policy, there is a greater need to further validate this effect to inform subsequent interventions.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there is evidence of a strong relationship between fatigue and the development of PTSS. Individuals who experience prolonged or severe fatigue, especially in the context of traumatic events such as the COVID-19 pandemic, are at an increased risk of developing PTSS [ 38 ]. This is evident in studies conducted on various populations, including military personnel, first responders, and healthcare workers, where those exposed to extreme fatigue due to long working hours, high stress, and overwhelming demands have shown a higher likelihood of developing PTSS [ 39 41 ].…”
Section: Introductionmentioning
confidence: 99%